Structure and conformation of polyetheramine in confined space of graphene oxide and its enhancement on the electrically conductive properties of monomer casting nylon-6. (April 2017) - Xiang, Meng; Li, Chengjie; Ye, Lin
Abstract: Graphene oxide (GO) was functionalized with polyetheramine (PEA) and MC nylon-6/reduced GO (rGO)-PEA composites were in situ synthesized. Intermolecular covalent and hydrogen bonding was confirmed to form for GO/PEA molecules, and the grafting ratio and average layer thickness exhibit a significant increase with PEA loading. Meanwhile the interlayer spacing (d002 ) of GO-PEA increases steadily, and PEA chains adopt trans and planar zigzag conformation with arrangements of monolayer, bilayer in GO layers in the range of 100–400% PEA, while the completely exfoliated state of GO formed by saturation intercalation of 700% PEA. Compared with GO, the layer stacking of GO-PEA is much more weakened, exhibiting a wrinkled and almost monolayer dispersion state, which leads to a good dispersion of GO (rGO)-PEA in melting caprolactam and a much higher uniformity for the nylon-6 composites. The electrically conductive network formed, resulting in the remarkably improved electrical conductivity of the composites.